A rapid and sensitive LC‐MS/MS method for the determination of Pulsatilla saponin D in rat plasma and its application in a rat pharmacokinetic and bioavailability study. (9th July 2014) - Ouyang, Hui; Guo, Yicheng; He, Mingzhen; Zhang, Jinlian; Huang, Xiaofang; Zhou, Xin; Jiang, Hongliang; Feng, Yulin; Yang, Shilin
Abstract A simple, sensitive and specific liquid chromatography–tandem mass spectrometry method was developed and validated for the determination of Pulsatilla saponin D, a potential antitumor constituent isolated from Pulsatilla chinensis in rat plasma. Rat plasma samples were pretreated by protein precipitation with methanol. The method validation was performed in accordance with US Food and Drug Administration guidelines and the results met the acceptance criteria. The method was successfully applied to assess the pharmacokinetics and oral bioavailability of Pulsatilla saponin D in rats. Copyright © 2014 John Wiley & Sons, Ltd.